Engineering Bacterial Surface Displayed Human Norovirus Capsid Proteins: A Novel System to Explore Interaction Between Norovirus and Ligands - Niu, Mengya; Yu, Qianqian; Tian, Peng; Gao, Zhiyong; Wang, Dapeng; Shi, Xianming (Frontiers in Microbiology, 2015)
Human noroviruses (HuNoVs) are major contributors to acute nonbacterial gastroenteritis outbreaks. Many aspects of HuNoVs are poorly understood due to both the current inability to culture HuNoVs, and the lack of efficient small animal models. Surrogates for HuNoVs, such as recombinant viral like particles (VLPs) expressed in eukaryotic system or P particles expressed in prokaryotic system, have been used for studies in immunology and interaction between the virus and its receptors. However, it is difficult to use VLPs or P particles to collect or isolate potential ligands binding to these recombinant capsid proteins. In this study, a new strategy was used to collect HuNoVs binding ligands through the use of ice nucleation protein (INP) to display recombinant capsid proteins of HuNoVs on bacterial surfaces. The viral protein-ligand complex could be easily separated by a low speed centrifugation step. This system was also used to explore interaction between recombinant capsid proteins of HuNoVs and their receptors. In this system, the VP1 capsid encoding gene (ORF2) and the protruding domain (P domain) encoding gene (3′ terminal fragment of ORF2) of HuNoVs GI.1 and GII.4 were fused with 5′ terminal fragment of INP encoding gene (inaQn). The results demonstrated that the recombinant VP1 and P domains of HuNoVs were expressed and anchored on the surface of Escherichia coli BL21 cells after the bacteria were transformed with the corresponding plasmids. Both cell surface displayed VP1 and P domains could be recognized by HuNoVs specific antibodies and interact with the viral histo-blood group antigens receptors. In both cases, displayed P domains had better binding abilities than VP1. This new strategy of using displayed HuNoVs capsid proteins on the bacterial surface could be utilized to separate HuNoVs binding components from complex samples, to investigate interaction between the virus and its receptors, as well as to develop an oral vaccine for HuNoVs.